Positive remodeling at 3 year follow up is associated with plaque free coronary wall segment at baseline: A serial IVUS study. - Wentzel, Jolanda J. (2014)
Aims At present it is unknown what limits the arterial remodeling process during atherosclerotic plaque formation. In healthy arteries remodeling is regulated by the shear stress induced response by the endothelium. As endothelium at the plaque site is assumed to be dysfunctional, we tested the hypothesis that plaque free wall (PFW) determines vascular remodeling during atherosclerotic plaque build-up. Methods & results 66 human coronary ROIs (38 patients) were studied at baseline and at 3 years follow up applying intravascular ultrasound (IVUS). From the IVUS images the lumen and external elastic membrane contours were delineated to assess wall thickness (WT), vessel area (VA), Plaque Area (PA) and plaque burden (PA/VA*100%). WT < 0.5 mm was defined as normal and determined the arc of the PFW (0–360°). Positive remodeling was defined as relative difference of VA over time >5%. At baseline, IVUS-PFW was inversely related to plaque burden (p < 0.05). Positive remodeling was most frequently observed in ROIs with IVUS-PFW > 180° (i.e. larger than half of the circumference) compared to PFW < 180° (55% vs. 12%, p < 0.05). Accordingly, plaques with IVUS-PFW > 180° at baseline had the largest change in VA (1.1 ± 2.1 vs. −0.4 ± 0.6 mm2, p < 0.05) with an odds ratio of 9.2 to develop positive remodeling. Conclusions Our serial IVUS data show that IVUS-PFW is a determinant of vascular remodeling. ROIs with PFW > 180 at baseline had the highest probability to undergo positive remodeling.